Pengaruh Literasi Ekonomi Dan Teman Sebaya Terhadap Perilaku Konsumtif Siswa Kelas Xi Ips Sma Jawaahirul Hikmah Besuki - Tulungagung Tahun Pelajaran 2020/2021 - Nur Lina; Imam Sukwatus Sujai (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2023)
This study aims to describe the influence of economic literacy and peers on the consumptive behavior of class XI Social Sciences students at SMA Jawaahirul Hikmah Besuki-Tulungagung for the academic year 2020/2021. This research method uses quantitative methods. The subjects of this research are all students of class XI Social Sciences SMA Jawaahirul Hikmah Besuki-Tulungagung Academic Year 2020/2021 with a population of 65 students with a sample of 56 students. The data collection method used a questionnaire / questionnaire that was tested for validity and reliability. Data analysis used multiple linear regression analysis. The results of this study indicate (1) there is a significant influence between economic literacy and consumptive behavior partially with t count 2.163 t table 2.006 (2) there is a significant influence between peers and partial consumptive behavior with t count 2.832 t table 2.006 (3) there is a significant effect between economic literacy and peers on consumptive behavior simultaneously with F count 14.424 F table 3.17. The results of the regression equation Y = 21.410 + 0.303X1 + 0.372X2.